Enhanced recovery after surgery (ERAS) for head and neck oncology patients. (7th February 2016) - Coyle, M.J.; Main, B.; Hughes, C.; Craven, R.; Alexander, R.; Porter, G.; Thomas, S.
Abstract : Objectives: To describe the development of an enhanced recovery after surgery (ERAS) protocol for people undergoing surgery for head and neck cancer. Design: Service improvement project. Participants: Head and neck oncology patients. Methods: The programme was developed in a series of structured meetings over a 6‐month period. Stakeholders included oral and maxillofacial surgeons, otolaryngologists, anaesthetists, dieticians, physiotherapists, speech and language therapists (SALT) and nursing staff. Based on evidence within current literature and a consensus among the group, an ERAS programme for head and neck surgery patients was formulated. A 12‐month study of compliance with the ERAS programme was undertaken from February 2014 to January 2015. Results: The process has resulted in the realisation of a head and neck ERAS programme. Key elements include a patient diary, nutritional optimisation, avoiding tracheostomy when possible, goal‐directed fluid therapy intra‐operatively and a specific head and neck postoperative pain management protocol. Overall compliance was high. Important areas showed lower levels of compliance – only 55% of people were given an explanation of the ERAS programme preoperatively, 75% took preoperative carbohydrate drinks, 10% had individualised goal‐directed fluid therapy, and 7% were mobilised in the first 24 h after surgery. The mean length of hospital stay was 14.55 days (sd 7.48). Conclusions: The ERAS programme developed is now embedded in the care pathway for people undergoing head and neck cancer surgery in our unit. The mean length of hospital stay has reduced since the introduction of the programme.